ANALYSIS OF THE SITUATION OF PEACE AND STABILITY IN LIBERIA FOURTEEN YEARS AFTER THE ESTABLISHMENT OF THE UNITED NATIONS MISSION IN LIBERIA (UNMIL) (Journal of the Spanish Institute for Strategic Studies, 2018)
The Liberian Civil War (1989-2003) ended in August 2003 with thesigning of the Accra Comprehensive Peace Agreement. Shortly thereafter,the United Nations Security Council established the United NationsMission in Liberia through Resolution 1509. Since then, the Governmentof the Republic of Liberia has depended on UNMIL’s military and policecomponents to maintain peace and stability in the country. Securityresponsibilities in the country were successfully handed over to theGovernment of the Republic of Liberia on 30 June 2016 as reported bythe United Nations Security Council Resolution 2333 (2016). However, adetailed analysis of the current situation of Liberia raises a serious concernregarding the possibility of lasting peace without the support of UNMIL.
Keywords: Americo-Liberians; ownership; State-building; peace-building; Government of the Republic of Liberia; Liberia; natives; top-down peace-building system; civil society; UNMIL